Effective chromium removal from water by polyaniline-coated electrospun adsorbent membrane - Dognani, Guilherme [UNESP]; Hadi, Pejman; Ma, Hongyang; Cabrera, Flavio C. [UNESP]; Job, Aldo E. [UNESP]; Agostini, Deuber L.S. [UNESP]; Hsiao, Benjamin S. (Elsevier, 2019)
Polyaniline (PAni)-coated polyvinylidenefluoride-co-hexafluoropropilene (PVDF-HFP)nanofibrous membranes were fabricated by electrospinning of PVDF-HFP followed by in-situ polymerization of PAni on the nanofiber surface. The resulting membranes with PAni coating were applied for chromium removal, where the efficiency was evaluated as functions of the pH value and adsorption time. Dynamic adsorption tests were also carried out at different flow rates and volumes of chromium in water. It was found that the PAni coating greatly enhanced the chromium removal efficiency with the maximum adsorption capacity being 15.08 mg/g at pH = 4.5. The desorption study further confirmed the recyclability of the PAni coated PVDF-HFP membrane showing an efficiency over 70% even after 5 cycles of usage. The structure and property relationships of these membranes were also characterized by FTIR spectroscopy, capillary flow porometer, water contact angle, scanning electron microscopy and X-ray photoelectron spectroscopy.
Keywords: Adsorbent membrane; Adsorption; Chromium removal; Electrospinning; Nanofibers; Polyaniline